2021
DOI: 10.22266/ijies2021.0430.43
|View full text |Cite
|
Sign up to set email alerts
|

Grey Wolf Optimization Parameter Control for Feature Selection in Anomaly Detection

Abstract: The performance of different mechanisms utilised to perform anomaly detection depends heavily on the group of features used. Therefore, dealing with a multi-dimensional dataset that typically contains a large number of attributes has caused problems to classification accuracy. Not all attributes in the dataset can be used in the classification process since some features may lead to low performance of classifiers. Feature selection (FS) is a good mechanism that minimises the dimension of high-dimensional datas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…In 2021, a method was proposed [ 27 ] to tackle anomaly detection problems by utilizing an enhanced grey wolf optimizer in feature selection of the multidimensional dataset by controlling the balancing parameter for exploration and exploitation. The parameter “ a ” is the main focus with its value increased or decreased depending on the current iterations' performance as compared to the previous iteration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 2021, a method was proposed [ 27 ] to tackle anomaly detection problems by utilizing an enhanced grey wolf optimizer in feature selection of the multidimensional dataset by controlling the balancing parameter for exploration and exploitation. The parameter “ a ” is the main focus with its value increased or decreased depending on the current iterations' performance as compared to the previous iteration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Single-based algorithms, including variable neighborhood search [13], simulated annealing [14], and guided local search [15], aim to improve a single candidate solution. By contrast, population-based algorithms maintain and enhance candidate solutions, often using population features to conduct direct search; such algorithms include biogeography-based optimization [16], grey wolf optimizer [17], particle swarm optimization (PSO) [18], emperor penguin colony [19], genetic algorithm (GA) [20], ant colony optimization (ACO) [21], black hole (BH) algorithm [22], and dragonfly algorithm (DA) [23]. In recent years, studies on plants have demonstrated that plants display intelligent behavior.…”
Section: Introductionmentioning
confidence: 99%
“…"Unsupervised" means that there is no predefined information about the form of the dataset. Generally, there are two ways to conduct the division of data into groups [2]: the deterministic approach, and the optimization approach. The former approach includes partitioned clustering, hierarchical clustering, density-based clustering, grid-based clustering, and model-based clustering [3].…”
Section: Introductionmentioning
confidence: 99%